Empowering an indigenous rural community: Local teachers for local schools - John Delany; Derek Wenmoth (Flexible Learning Association of New Zealand, 2012)
POLO is the name given by the Christchurch College of Education to the distance delivery of three-year primary teacher education to students all over New Zealand. These are students who wish to train for teaching but are prevented from doing so because of where they live. POLO also involves others who wish to train without having to attend on-campus as a full-time face-to-face student. The innovative nature of this programme includes the establishment of a group of students, mainly indigenous New Zealanders, in the Hokianga, one of New Zealand's most isolated and economical! y disadvantaged areas. The four-year programme, from which students graduated at the end of 2000, uses mainly print-based courses combined with communications technologies. This paper explores how the programme was adapted to meet specific local needs relating to Maori language and culture, and describes how particular features of the programme have become a catalyst for the empowerment of individuals, the local community, and beyond.